Intelligence level in children with cerebral palsy (CP) at YPAC Medan (Faculty of Medicine Universitas Indonesia, 2002)
Children with cerebral palsy has been investigated at YPAC (Yayasan Pembinaan Anak Cacat / Institute for Crippled Children) Medan to obtain the detailed description of patientâs intelligence level referring to cerebral palsy types and to determine the relationship between palsy types and mental retardation level as well as to relate cerebral palsy types and sex. The study is cross-sectionally conducted involving all cerebral palsy patients listed in registration book of YPAC Policlinic Medan from July 1987 to June 1998. Of 74 patients participated in the study, all had IQ under average and 62% them were female. The most common type is spastic (65%), followed by mixed (16%), dyskinetic (11%) and hypotonic (8%), respectively. Overall, the mixed type had severe mental retardation. Statistically, there is a significant relationship between cerebral palsy types and mental retardation level (p < 0.001). There is no significant relationship between cerebral palsy types and sex. (Med J Indones 2002; 11: 242-5)Keywords: cerebral palsy, intelligence level, children with CP